Monitoring Regional Oxygen Saturation for Early Detection of Leg Ischemia (Revista de Medicina Clinica, 2024)
Clinical Snapshot on "Role of Regional Oxygen Saturation in the Early Detection of Lower Extremity Ischemia" presented in Volume 8 Issue 1 of Revista de Medicina Clínica.
Keywords: Regional Oxygen Saturation; Leg Ischemia